Pengelolaan Aset Terlantar Sebagai Balai Latihan Kerja (BLK) di Pondok Pesantren Adnan Al Charish Bojonegoro Menurut Perspektif Hukum Ekonomi Syariah - Alfinatur Rohmah; Agus Sholahudin Shidiq; Muhammad Zaenal Abidin (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2025)
Purpose - Islamic boarding schools have great economic potential through asset management, but there are still many Islamic boarding schools that face the problem of property or abandoned land that has not been utilized optimally. This study aims to analyze the management mechanism of abandoned land at the Adnan Al Charish Islamic Boarding School in Bojonegoro from the perspective of Maqashid Syariah and evaluate its impact on the economic welfare of students. Method - This study uses a qualitative approach with a single case study design. Data were obtained through in-depth interviews, participatory observations, and documentation studies. Results - The results of the study show that the management of abandoned land is carried out through asset legalization, land conversion into Job Training Center (BLK), establishment of Enterprises Owned by Islamic Boarding Schools, and multimedia training for students. In the perspective of Maqashid Sharia, this management reflects the principles of hifz al-mal through asset optimization and hifz al-'aql through increasing the capacity and skills of students. The resulting economic impact encompasses increased institutional income for pesantren, strengthened economic independence, employment generation, and improved student welfare through supplementary revenue streams and educational financing support mechanisms. Implications - This study contributes to the literature by demonstrating that Maqashid Sharia-based abandoned land management can function as a strategic model for achieving sustainable economic independence and improving student welfare in Islamic boarding schools.